Gender Stereotypes in Marriage: A Case Study of Syarifah and Non-Sayyid Marriage in Palu City - Alatas, Raisa; Sari, Riska Fitrah (NALAR, 2024)
This article examines the dynamics of intercultural marriage in the Bani Alawiyyin community in Palu City, which involves gender stereotypes, cultural identity, and social norms. This study aims to describe in detail the influence of gender stereotypes on perceptions and expectations in marriage between Syarifah women and non-Sayyid men in Palu City. The method used is qualitative research with a case study approach aimed at examining the natural conditions of the research object. The snowball sampling technique was applied to determine the research object, resulting in 8 informants of two Ulama and three married couples. The findings suggest that Syarifah and non-Sayyid couples are under pressure to maintain their family identity. Isolation from the family, especially the Syarifah from the family of origin, creates social pressure. At the same time, the Arab Hadramaut cultural identity is still maintained in the family even though the couple practices mixed marriages. Differences in views regarding marriage between Syarifah women and non-Sayyid men give rise to tension and conflict in interpersonal and social relations among Arab Hadramaut in Palu City. However, cultural assimilation and social changes influence perceptions and attitudes toward intercultural marriage.